Is there a role for gut microbiota in type 1 diabetes pathogenesis? - Bibbò, Stefano; Dore, Maria Pina; Pes, Giovanni Mario; Delitala, Giuseppe; Delitala, Alessandro P. (Annals of medicine (Helsinki), 2017)
Type 1 diabetes mellitus (T1D) is an autoimmune disease characterized by insufficient insulin production due to the destruction of insulin secreting β-cells in the Langerhans islets. A variety of factors, including chemicals, viruses, commensal bacteria and diet have been proposed to contribute to the risk of developing the disorder. In the last years, gut microbiota has been proposed as a main factor in T1D pathogenesis. Several alterations of gut microbiota composition were described both in animal model and in humans. The decrease of Firmicutes/Bacteroides ratio was the most frequent pattern described, in particular, in human studies. Furthermore, Bacteroides, Clostridium cluster XIVa, Lactobacillus, Bifidobacterium, and Prevotella relative abundances were different in healthy and affected subjects. Dysbiosis would seem to increase intestinal permeability and thus promote the development of a pro-inflammatory niche that stimulates β-cell autoimmunity in predisposed subjects. Preliminary studies on animal models were realized to investigate the role of gut microbiota modulation as therapy or prevention approach in predisposed animals: promising and stimulating results have been reported. Key message Dietary antigens and microbiota-derived products might act as triggers of T1D by causing a pro-inflammatory and metabolic dysfunctional environment.